Probiotics and Prevention of Pediatric Upper Respiratory Tract Infections. (September 2013) - Principi, N.; Tagliabue, C.; Tenconi, R.; Esposito, S.
There is a certain consensus that some probiotics can significantly help in preventing and relieving the symptoms of gastrointestinal diseases and atopic diseases in general, but their use in respiratory tract infections has only been marginally investigated. The main aim of this review is to evaluate what is known about the impact of probiotics on pediatric respiratory tract infections in order to verify whether more data are needed before they can be used on infants and children with respiratory problems. Analysis of the literature shows that our knowledge is limited to the prevention of upper respiratory tract infections (URTIs). The very few studies carried out so far seem to indicate that probiotic administration may have some advantages in this regard, but the great limitation is that nothing is known about the susceptible micro-organisms or treatment regimens. Furthermore, URTIs are very limited clinical problems and it seems unreasonable to use a treatment whose efficacy and safety has not been completely clarified as means of preventing them. No data are available concerning the treatment of URTIs. There is a need for further research into the role of probiotics in treating respiratory infections and preventing more severe respiratory problems, including those involving the lower respiratory tract.